2018
DOI: 10.4148/2378-5977.7688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Increased Pork Hot Carcass Weights and Chop Thickness on Consumer Visual Appearance and Purchase Intent Ratings of Top Loin Chops

Abstract: The objective of this study was to evaluate the effect of increased pork hot carcass weights on consumer visual acceptability and purchase intent of top loin chops cut to various thicknesses in a price labeled versus unlabeled retail display scenario. Pork loins (n = 200) were collected from 4 different hot carcass weight groups: a light weight group (less than 246.5 lb; LT), medium light weight group (246.5 to 262.5 lb; MLT), medium heavy weight group (262.5 lb to 276.5 lb; MHVY), and heavy weight group (276.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several recent studies and market assessments have indicated that the weight of pork carcasses is expected to increase in upcoming years ( Morin et al, 2015 ; Harsh et al, 2017 ; Rice et al, 2018 ; Gilleland et al, 2019 ; Price et al, 2019 ). Harsh et al (2017) goes as far as to state predictions for carcass weights in the future, which were stated as 104 kg in 2030, 111 kg in 2040, and 118 kg in 2050.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies and market assessments have indicated that the weight of pork carcasses is expected to increase in upcoming years ( Morin et al, 2015 ; Harsh et al, 2017 ; Rice et al, 2018 ; Gilleland et al, 2019 ; Price et al, 2019 ). Harsh et al (2017) goes as far as to state predictions for carcass weights in the future, which were stated as 104 kg in 2030, 111 kg in 2040, and 118 kg in 2050.…”
Section: Resultsmentioning
confidence: 99%
“…Trained panelists were oriented to evaluating pork chop palatability over 5 training sessions prior to data collection. Details regarding the anchors and training procedures used are outlined by Rice (2019) . Chops used for trained sensory analysis were thawed overnight at 4 °C and cooked as described above.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, it is worth noting that the consumer attractiveness of pig corpses, as determined by initial visual assessment by consumers, is dependent on pre-slaughter live weight and increases considerably ( p < 0.05) as live weight climbs to higher weight categories (125 kg) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%